Unusual presentation of scrub typhus in pregnancy with postpartum dilated cardiomyopathy: a case report - Agarwal, Ashita; Sharma, Madhu Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Though scrub typhus is one of the uncommon causes of fever in peripartum period it must be kept in differential diagnosis of any febrile illness particularly when the signs and symptoms points towards rickettsial etiology. Weil-Felix test can be used for diagnosis. Uncommon complications such as cardiomyopathy must be suspected in cases who present with undue dyspnea and signs of congestive heart failure. Patients with cardiomyopathy needs appropriate management in intensive care units. ECG and 2D echocardiography (2D echo) needs to be done in these patients which may show arrhythmias and ventricular hypokinesia and decreased ejection fraction respectively. A 21 years aged first gravida female at 34 weeks of gestational age was admitted with complaints of high-grade fever since 4-5 days with no previous antenatal visits. A diagnosis of rickettsial fever was suspected on the basis of presenting complaints and clinical examination. Weil-Felix test turned out to be positive with OX19 titre of 1:160. She underwent LSCS in view of fetal distress and delivered a healthy male child. In immediate postpartum period she developed respiratory distress. Her 2D echo showed features suggestive of dilated cardiomyopathy. She was managed in medical intensive care unit and was eventually discharged. Though uncommon rickettsial diseases should be kept in the differential diagnosis of any febrile illness particularly when presenting with characteristic rash. Serious complications such as cardiomyopathy must be diagnosed early and treated appropriately in these patients to prevent mortality.